Nocturnal Eyes in Slipper Lobsters (Decapoda Scyllaridae): Physiological and Ecological Implications of Habitat Depths for Visual Traits - Hayasaka, Oki; Chang, Hao-Yi; Li, Li-Chun; Tseng, Yung-Che; Shao, Yi Ta (Frontiers in Marine Science, 2022)
The light characteristics of an ecosystem drive evolutionary adaptations in visual traits, enhancing the diversity and abundance of species living there. The visual systems of crustaceans are highly diverse and often correspond to the optical properties of their preferred environments. Although habitat depth is known to greatly influence visual specialization in marine crustaceans, it remains unclear whether depth drives visual adaptions in nocturnal species. Slipper lobsters (Scyllaridae) are nocturnal benthic marine crustaceans distributed throughout a wide range of depths. In order to understand the visual adaptive capabilities of slipper lobsters inhabiting different depths, we characterized the eye structures of a shallow-water species (Parribacus japonicas), an intermediate-depth species (Scyllarides squammosus) and a deep-water species (Ibacus novemdentatus). Moreover, we measured by electroretinogram (ERG) the spectral sensitivities and temporal resolutions for each species using the following light stimuli: UV (λmax 386 nm), blue (λmax 462 nm), green (λmax 518 nm), yellow (λmax 590 nm), and red (λmax 632 nm). Our histological experiments show that all three species possess a typical superposition compound eye with square facets, and their ERG measurements revealed a single sensitivity peak for each species. Notably, peak spectral sensitivity corresponded to habitat depth, with the estimated peak for I. novemdentatus (493.0 ± 9.8 nm) being similar to that of S. squammosus (517.4 ± 2.1 nm), but lower than that of P. japonicus (537.5 ± 9.9 nm). Additionally, the absolute sensitivities at respective peak wavelengths for I. novemdentatus and P. japonicus were higher than that of S. squammosus. No differences were observed among the three species for maximum critical flicker fusion frequency (CFFmax) across light stimuli. However, P. japonicus had lower CFFmax values than the other two species. These data suggest that all three nocturnal slipper lobsters are likely monochromatic and well adapted to dim light environments. Significantly, the deep-water slipper lobster displayed higher spectral sensitivities at shorter wavelengths than the shallow water species, but temporal resolution was not compromised.